BIMBINGAN BELAJAR BAGI SISWA SEKOLAH DASAR SELAMA MASA PANDEMI COVID-19 DI DUSUN TAWARSARI - Aprillia Ratna Sasmita; Entoh Tohani (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Tutoring is one of the efforts to solve problems in a guided manner to achieve maximum learning goals. During the pandemic, learning activities cannot be carried out optimally. This is caused by changes in student learning which were carried out offline at school to be online or carried out independently from home. The application of independent learning is seen as ineffective because the phenomenon is that students, especially at the elementary school level, use their free time more by playing and doing activities outside of learning activities. This has an impact on the less than the optimal process of material absorption and students' cognitive development to be able to accept learning. Therefore, it is necessary to have a guided tutoring effort to maximize the process of student teaching and learning activities that are carried out independently from home.